2010
DOI: 10.1038/labinvest.2010.50
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of epimorphin in the repair of experimental renal fibrosis in mice

Abstract: Interaction between epithelial cells and mesenchymal cells is essential in normal organ morphogenesis and in tissue repair after injury. Epimorphin, a mesenchymal protein that regulates epithelial morphogenesis through epithelialmesenchymal interactions, has recently attracted attention as an important modulator of tissue repair. In this study we analyzed the role of epimorphin in renal fibrosis. We first found a progressive increase in epimorphin expression corresponding to the progression of renal fibrosis i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 43 publications
3
15
0
Order By: Relevance
“…It has been associated with resolution of fibrosis in both kidney and liver by inducing protease expression to cause ECM degradation [22], [24]. In line with this, we detected altered MMP/TIMP expression in activated rHSCs treated with rhEPIM (Fig.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…It has been associated with resolution of fibrosis in both kidney and liver by inducing protease expression to cause ECM degradation [22], [24]. In line with this, we detected altered MMP/TIMP expression in activated rHSCs treated with rhEPIM (Fig.…”
Section: Resultssupporting
confidence: 82%
“…However, in models of liver regeneration, Epim also appears to increase later in HSCs highlighting a potential role during the recovery phase of tissue repair [21][23]. In line with this, a feature of EPIM in both renal and liver fibrosis is its ability to induce protease expression favoring collagen degradation and resolution of fibrosis [22], [24], [25]. Although this provides clues of EPIM's role in modulating the ECM in fibrosis the mechanisms by which it acts and is regulated are less clear.…”
Section: Introductionmentioning
confidence: 85%
“…Epim interacts with ␣V-integrins on target epithelial cells (13), affecting downstream signaling pathways that induce branching morphogenesis and regulating transcription of multiple target genes, including MMPs (6). Relevant to the present observations are studies in kidney that showed that Epim is expressed in interstitial myofibroblasts and Epim protein abundance increases in response to urinary obstructive injury; blocking Epim signaling with an anti-Epim antibody increases TGF-␤ mRNA expression in kidney during the injury recovery phase (36). Herein, we have shown that lack of Epim signaling in the gut in Apc min/ϩ mice also results in increased mucosal TGF-␤ expression.…”
Section: Discussionsupporting
confidence: 63%
“…For example, exposure of mammary epithelial cells to Epim resulted in increased expression of genes associated with branching morphogenesis in the mammary gland, such as matrix metalloproteinase (MMP)-3, and downregulation of luminal epithelial markers, such as keratin-16 (6). Also, administration of an anti-Epim-blocking antibody to mice in a kidney injury model resulted in increased transforming growth factor-␤ (TGF-␤) and decreased MMP-2 and MMP-9 expression (36).…”
mentioning
confidence: 99%
“…More recent studies suggest that consistent detection of this protein may be best achieved by immunostaining on frozen versus paraffin embedded sections. 41 …”
Section: Discussionmentioning
confidence: 99%